Effects of Nitrate Enrichment on Respiration, Photosynthesis, and Fatty Acid Composition of Reef Coral Pocillopora damicornis Larvae - Liu, Cheng-Yue; Zhang, Fang; Sun, You-Fang; Yu, Xiao-Lei; Huang, Hui (Frontiers in Marine Science, 2020)
In the foreseeable future, coastal coral reef ecosystems are likely to face further increases in eutrophication. Lipids and fatty acids (FAs), as important components of corals, are becoming a hot topic to study the effects of eutrophication on corals. This study investigated the effects of nitrate (NO3–) enrichment (0, 5, 10, 20, and 40 μM) on the respiration, photosynthesis, and FA compositions of Pocillopora damicornis larvae. Our results showed that saturated FAs (SFAs) were the most abundant in P. damicornis larvae over all treatment groups, followed by polyunsaturated FAs (PUFAs). The unsaturated-to-SFA ratio (U/S) and unsaturation index (UI) reduced at low nitrate concentrations (<10 μM), since the level of SFAs (mainly 16:0 and 18:0) increased whereas PUFAs (mainly 18:3n3, 20:3n6, and 22:6n3) decreased. Consequently, the biomembranes of the larvae may have become more rigid and viscous, which slowed excessive nitrate entry. Moreover, significantly enhanced photosynthetic functions of zooxanthellae in larvae were found in the N5 group (5 μM). However, the opposite FA patterns were observed in P. damicornis larvae at higher nitrate concentrations (>20 μM). The UI and U/S levels were elevated due to the increased PUFAs levels and decreased SFA levels at higher nitrate concentrations. Compared with the N5 and N10 groups, the fluidity of the biomembrane of the larvae did not continue to decrease but instead increased at higher nitrate concentrations, indicating that the biomembrane restructuring in the larvae may have become ineffective. Moreover, respiration increased and the consumption of numerous lipids led to a significant decrease in TFAs. These could adversely affect the dispersal, settlement, and development of larvae. Overall, P. damicornis larvae can adapt to low levels of nitrate (<10 μM) due to biomembrane restructuring through changes in FA composition. However, negative effects occur in larvae when nitrate exceeds 20 μM.